Contribution of Multimedia and Self-Efficacy towards Students’ Speaking Performance: Correlational Study - Sri Endah Kusmartini (Jurnal Bahasa Inggris Terapan, 2022)
This current research regarding the contribution of multimedia in academic context and self-efficacy towards students’ speaking performance was a quantitative correlational study. The population of the research was engineering students of State Polytechnic of Sriwijaya in the academic year of 2021-2022. The number of the sample were 140 respondents. The data were collected through questionnaire, interview and speaking test. The data were analyzed by using descriptive analyses, Pearson Product Moment Coefficient Correlation, Linear Regression, and Compare Means. The result showed that multimedia and efficacy contributed significantly to students’ speaking performance. The result also showed that there was no significant mean difference in self-efficacy of engineering students on the basis of gender. Some points need to be considered. First, support the students with suitable media for each learning process. Second, facilitate them with reliable multimedia that can increase the interactions and interest to learn English, especially speaking. Third, warn them about the misuse of multimedia and remind them the function of multimedia in the learning process. Fourth, all parties involved in the learning process of speaking must do their best to improve the students' speaking performance. Fifth, simultaneously consider the variables of multimedia usage and self-efficacy to improve the students' speaking performance.